The Concepts of Prevalence and Incidence as Applied to the Study of Development and Duration of Disease - Kashgahian, M. (Methods of Information in Medicine, 1968)
The proper use of prevalence and incidence data can result in an effective way to study the history of the disease process. Methodology is given whereby the progression, duration and transition of diseases can be elucidated. Prevalence and incidence have been redefined and used in an unconventional way in view of new types of data which are being generated by mass screening projects for disease which are able to discover presymptomatic and preclinical disease states.Die richtige Verwendung von Prävalenz- und Inzidenz-Daten kann wichtige Hinweise zur Untersuchung der Vorgeschichte eines Krankheitsprozesses liefern. Die vorliegende Arbeit gibt die Methodik an, mittels derer Verlauf, Dauer und Stadienwandel von Krankheiten aufgehellt werden können. Die Begriffe Prävalenz und Inzidenz werden neu definiert und in unkonventioneller Weise auf neue Datentypen angewandt, die aus vorbeugenden Screening-Projekten mit dem Ziel der Erkennung präsymptomatischer und präklinischer Krankheitsstadien gewonnen werden.